Pedagogical problems of ecologocal (environmental) training in technical universities - SAYENKO, Tatiana; NAGORNIUK, Oksana; NEDOBIJCHUK, Lilija (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The ways of modernization of ecological or environmental education in high technical school during the competency paradigm and in final phase of the Decade of Education for Sustainable Development (2011–2014) were discussed